Metasurface-assisted phase-matching-free second harmonic generation in lithium niobate waveguides - Cheng Wang (Nature Portfolio, 2017)
Phase matching is a crucial condition for nonlinear optical processes. Here, Wang et al. demonstrate that a gradient metasurface composed of phased array antennas allows phase-matching-free frequency conversion over a pump wavelength range of almost 100 nm.